The Effect of Work Motivation, Workload and Job Training on the Performance of Army and Civil Servants of the V/Brw Finance of Military Regional Command - Saptawaty, Elia; Sembiring, Ferikawita Magdalena (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Achmad Yani, 2026)
Every month, Finance Officer of Rank II - IV of Kudam V/Brw get assessment results as a form of job evaluation. During January 2023 to March 2024, the phenomenon of Paku Satker's performance appraisal showed results that were not optimal so it was necessary to analyze the indicators that influenced this performance. The purpose of this study was to determine the effect of Work Motivation, Workload and Job Training on Performance of Soldiers and Civil Servants of Kudam V / Brw. This research uses quantitative methods. The object of research amounted to 175 respondents. The results of statistical analysis on partial tests show that Work Motivation and Job Training have a positive effect while Workload has no effect on Performance. Furthermore, the simultaneous test shows that Work Motivation, Workload and Job Training affect performance. It can be concluded that increasing Work Motivation and Job Training and decreasing Workload can improve the Performance of Soldiers and Civil Servants of Kudam V / Brw.